The benefits of physical activity for old and young - Tjan, Richard (Universa Medicina, 2010)
There is now ample scientific evidence that elderly persons, will benefit from physical activity in a similar manner as the younger generations. Regular physical activity of at least moderate intensity reduces the risk of cardiovascular major events, leading to the conclusion that physical inactivity is a major cardiovascular risk factor. The underlying molecular mechanism may be that moderate physical activity leads to a reduction of oxidative stress.(1) In a prospective cohort of 21,094 men (mean age, 53 years) without known coronary heart disease at baseline in the Physiciansâ€™ Health Study, it was shown that vigorous physical activity (defined as â€˜exercise to the point of breaking a sweatâ€™) was associated with a decreased risk of heart failure, whereas elevated BMI (even in the pre-obese range) was associated with an increased risk.(2) Numerous studies have also demonstrated the benefits of daily physical activity for the elderly in maintaining functional independence, defined as â€˜the capacity to carry out activities of daily livingâ€™. Paterson and Warburton in 2010 conducted a systematic review of the relationship between physical activity of healthy community-dwelling elderly (age range 66 - 84 years) and functional limitations, disability, or loss of independence by analysis of prospective cohort studies reported in the literature. Among 2,309 citations from electronic bibliographical databases (MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane Library, SportDiscus) the investigators analyzed 66 prospective studies and concluded that â€œregular aerobic activity and short-term exercise programmes confer a reduced risk of functional limitations and disability in older ageâ€.